Using Force Plates to Monitor the Recovery of Vertical Jump Performance After Strenuous Exercise: A Systematic Review and Meta-Analysis - Caden Williams; Katherine Sullivan; Changki Kim; Lee J. Winchester; Michael V. Fedewa (Journal of Functional Morphology and Kinesiology)
Background: Force plates are commonly used as a non-fatiguing measure of recovery. However, the recovery time course captured via the force plate assessment of vertical jumps has yet to be established. Therefore, the objective of this systematic review and meta-analysis was to examine the change in vertical jump performance and the time course of recovery following an acute bout of strenuous exercise using force plates. Methods: Peer-reviewed articles (n = 22) published prior to 8 November 2023, were identified by searching three electronic databases (PubMed, Scopus, Web of Science). Studies included in this review met the following criteria: (1) available in English; (2) involved adult participants >18 years of age; (3) measured the change in vertical jump performance over consecutive days using a force plate system. Individual effect sizes (ESs) were calculated by dividing the change in vertical jump at each timepoint (24 h, 48 h, etc.) by the pooled standard deviation (SD), and they were aggregated using a three-level random-effects model. Results: Vertical jump performance decreased following an acute strenuous exercise bout (ES = −0.2639; p < 0.0001) and returned to baseline after 3 days of recovery, with larger decreases observed when assessed using Peak Height rather than Peak Power (ES = −0.4687 vs. ES = −0.1399; p = 0.0393). Older participants showed a larger decrease in vertical jump (β = −0.0489; p < 0.0001). Conclusions: Force plates can be used to evaluate recovery post-exercise, with a decline in performance on Days 1 and 2, and full recovery by Day 3. The findings from this study support the use of force plates for the evaluation of recovery.